2020
DOI: 10.1016/j.chom.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Heterogeneity of the Gut Limits Predation and Fosters Coexistence of Bacteria and Bacteriophages

Abstract: Bacteria and their viruses, bacteriophages (phages), are the most abundant components of the mammalian gut microbiota where these two entities coexist over time. The ecological dynamics underlying the coexistence between these two antagonistic populations in the gut are unknown. We challenged a murine synthetic bacterial community with a set of virulent phages, to study the factors allowing phages-bacteria coexistence in the gut. We found that coexistence was neither dependent on an arms race between bacteria … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 88 publications
(86 reference statements)
10
124
1
1
Order By: Relevance
“…It remains unclear what mechanisms are responsible for the long-term persistence and high prevalence of crAss-like phages in the human gut. Several mechanisms of phage persistence are possible, including spatial heterogeneity of microbial habitats in the gut (Lourenço et al, 2020), physiological stochasticity of phage sensitivity phenotype in their host bacteria (Lourenço et al, 2018), reversible genetic switching (phase variation) of surface receptor expression (Porter et al, 2020), constant sweeps of new mutations leading to arms race co-evolution with their hosts (Scanlan, 2017), or perhaps, an unusual life cycle (carrier state infection, pseudolysogeny) of the viruses themselves. Establishing these mechanism(s) is a challenging task due to the lack of tools for genetic manipulation, and the low similarity of crAss-like phage genomes and proteins to well characterised model viruses (Dutilh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear what mechanisms are responsible for the long-term persistence and high prevalence of crAss-like phages in the human gut. Several mechanisms of phage persistence are possible, including spatial heterogeneity of microbial habitats in the gut (Lourenço et al, 2020), physiological stochasticity of phage sensitivity phenotype in their host bacteria (Lourenço et al, 2018), reversible genetic switching (phase variation) of surface receptor expression (Porter et al, 2020), constant sweeps of new mutations leading to arms race co-evolution with their hosts (Scanlan, 2017), or perhaps, an unusual life cycle (carrier state infection, pseudolysogeny) of the viruses themselves. Establishing these mechanism(s) is a challenging task due to the lack of tools for genetic manipulation, and the low similarity of crAss-like phage genomes and proteins to well characterised model viruses (Dutilh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…If kill-the-winner dynamics occur at a strain or sub-strain level, stability is maintained at the species or genus taxonomic levels over time or it is possible that these phages engage in “piggyback-the-winner” dynamics (Silveira and Rohwer, 2016 ; Breitbart et al, 2018 ). The spatial heterogeneity of the gut also provides hosts with phage-inaccessible reservoirs in microhabitats creating source-sink dynamics that reduce selective pressures and allow the coexistence of both (Lourenço et al, 2020 ). Additionally, the oscillation of bacteria between phage-permissive and non-permissive phenotypes could also have an important role in this persistence (Porter et al, 2020 ).…”
Section: Current Methodologies Challenges and Potential Solutionsmentioning
confidence: 99%
“…An example of such spatial heterogeneity was identified in a study of virulent phage-bacteria coexistence in the gut using a murine model. It was found that the examined phages were in lower abundance in the mucosa while bacterial counts were high and vice versa in the lumen, thus, creating a luminal-mucosal gradient of phages and bacteria (Lourenço et al, 2020 ). In this example, the mucosa (source) was described as a phage-inaccessible refuge for the bacteria from where they can gradually disseminate into the lumen (sink) and phage predation occurs.…”
Section: Phage-host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b and S5), despite the fact that Prevotella are able to degrade mucins and are equipped to colonise the mucosa 26 . Theoretically, the relative abundance of Lak phages compared to Prevotella might also be higher in the mucosa compared to the lumen, because adhesion of phages to the mucosa should increase phage-bacteria encounter rates 27,28 . The finding that this is not the case may relate to the counteracting effect of the mucosa allowing bacteria to evade phage predation 27,28 .…”
Section: Distribution Of Lak Phage Andmentioning
confidence: 99%